2022
DOI: 10.1002/admt.202101360
|View full text |Cite
|
Sign up to set email alerts
|

Highly Durable Membrane Electrode Assembly with Multiwalled Carbon Nanotubes/CeO2‐Reinforced Nafion Composite Membrane by Spraying Method for Fuel Cell Applications

Abstract: membrane fuel cells (PEMFCs) use the chemical energy of both hydrogen and oxygen to generate electricity with high efficiency, zero pollution, and rapid start-up/shut-down at relatively low temperatures (<100 °C). [1,2] Because of these attractive characteristics, PEMFCs have considerable potential as power sources for diverse applications, particularly in automobiles; With the motivation, many manufacturers have successfully commercialized these applications. However, some critical issues, such as high cost, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…MEA Chemical Durability Test under Accelerated OCV Holding Condition: An accelerated OCV holding test was conducted for 120 h by supplying partially humidified H 2 and O 2 with the same flow rate of 300 sccm at 90 °C under RH 30 % condition. [34,64,76] After the OCV holding test, the drain water from the anode and cathode was collected to analyze the concentration of the total eluted fluorine ions. The I-V polarization curves, EIS, and linear sweep voltammetry (LSV) were measured before and after the protocol.…”
Section: Methodsmentioning
confidence: 99%
“…MEA Chemical Durability Test under Accelerated OCV Holding Condition: An accelerated OCV holding test was conducted for 120 h by supplying partially humidified H 2 and O 2 with the same flow rate of 300 sccm at 90 °C under RH 30 % condition. [34,64,76] After the OCV holding test, the drain water from the anode and cathode was collected to analyze the concentration of the total eluted fluorine ions. The I-V polarization curves, EIS, and linear sweep voltammetry (LSV) were measured before and after the protocol.…”
Section: Methodsmentioning
confidence: 99%
“…EIS measurements were conducted under a constant current of 0.1 mA, with an amplitude of 0.01 mA over 1 MHz to 1 Hz by supplying fully humidified nitrogen gas at 70 °C. The membranes’ in-plane conductivities were calculated using the measured EIS resistance and the following equation: σ = L italicRA where L (cm), R (Ω), and A (cm 2 ) represent the distance between the electrodes, resistance of the membrane, and cross-sectional area of the membrane, respectively. The chemical states of the membranes were examined using X-ray photoelectron spectroscopy (XPS) (Kratos, United Kingdom).…”
Section: Methodsmentioning
confidence: 99%
“…Apertures. The fabrication process of a polymeric stencil has been described in detail in the previous paper 26 and is summarized here. First, to prepare a polydimethylsiloxane (PDMS) mold with microsized pillar arrays (diameter 20 μm), a curing agent and base (Sylgard 184 kit, Dow Corning) were mixed in a weight ratio of 1:10 and poured onto the prepared silicon master with microsized holes (diameter 20 μm) and cured at 80 °C for 1 h. A flat PDMS mold was prepared similarly on a flat silicon master.…”
Section: Constructing a Polymeric Stencil Mask With Microsizedmentioning
confidence: 99%
“…30,31 Previous studies have shown that a tight attachment between the membrane and catalyst is conducive to improving the catalyst utilization efficiency of the MEAs. [32][33][34] We here systematically studied the effect of Pt loading on the single-cell performance of the two MEAs. Fig.…”
Section: Effect Of Pt Loading On the Performance Of The Meamentioning
confidence: 99%